Smoking cessation and prognosis during long-term follow-up after stroke, TIA, and acute coronary syndrome-results from the randomized controlled NAILED trial. - Anna-Lotta Irewall; Lina Åslund; Joachim Ögren; Thomas Mooe (PLoS ONE)
Background and aims About 50% of patients continue to smoke after stroke and myocardial infarction. We aimed to assess the effect of a multiple risk factor intervention on long-term smoking cessation and to explore a possible association between early smoking cessation and long-term prognosis. Material and methods Consecutive patients with stroke/TIA/acute coronary syndrome (ACS) at Östersund Hospital during 2010-2014 were included, randomized to intervention or usual care (1:1), and followed through 2017. This substudy included participants that reported current smoking during hospitalization and were alive at 1 month post discharge when the intervention began (n = 321). The smoking cessation intervention was part of a telephone-based, multiple risk factor intervention delivered by a nurse and consisted of brief advice delivered annually. Smoking cessation at the last follow-up was analyzed as the primary outcome. Smoking cessation at other time points and association between early smoking cessation and prognosis (CV events, survival) were secondary outcomes. Result After a mean follow-up of 4.2 years, 171 participants reported nonsmoking, with no significant difference between the intervention and control group (50.3% vs. 56.3%, absolute difference 5.9%, 95% CI -5.0 to 16.7, p = 0.286). Of these, 80.7% had stopped smoking within 1 month after discharge. The intervention did not improve smoking cessation proportions in the long or short term, and there was no apparent effect on smoking cessation attempts or sustained abstinence. Smoking cessation within 1 month was associated with lower all-cause mortality (HR 0.52, 95% CI 0.32-0.87), and there was a nonsignificant trend towards a lower incidence of CV events (HR 0.71, 95% CI 0.45-1.12). Conclusion Annual brief advice by a nurse as part of a multiple risk factor follow-up did not improve long-term smoking cessation after stroke/TIA/ACS. Continued smoking past 1 month was associated with worse prognosis. Trial registration ISRCTN registry ISRCTN96595458, ISRCTN23868518, ISRCTN30433343.